2022
DOI: 10.3390/app12042133
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Occurrence and Fate of Microplastics in WWTPs: A Case Study in Southwest Europe

Abstract: Microplastic (MP) water pollution is a major problem that the world is currently facing, and wastewater treatment plants (WWTPs) represent one of the main alternatives to reduce the MP release to the environment. Several studies have analysed punctual samples taken throughout the wastewater treatment line. However, there are few long-term studies on the evolution of MPs over time in WWTPs. This work analyses the performance of a WWTP sited in Southwest Europe in relation with annual occurrence and fate of MPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 79 publications
(146 reference statements)
1
6
0
1
Order By: Relevance
“…The fact is that the amount of microplastic is highest in warmer conditions than in colder ones. It has been shown that wastewater samples contain fragments of PP and PE, whereas sludge contains PA, PET, and PS, as denser polymers are deposited during the treatment process [ 85 ]. Studies have also shown that a human can ingest between 39,000–520,000 microplastic per year through food and beverages, with levels naturally depending on age and gender [ 86 ].…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…The fact is that the amount of microplastic is highest in warmer conditions than in colder ones. It has been shown that wastewater samples contain fragments of PP and PE, whereas sludge contains PA, PET, and PS, as denser polymers are deposited during the treatment process [ 85 ]. Studies have also shown that a human can ingest between 39,000–520,000 microplastic per year through food and beverages, with levels naturally depending on age and gender [ 86 ].…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…Most of these microparticles end up in sewage systems which are one of the main culprits of MP release into the environment (Horton et al 2017 ; Padervand et al 2020 ; Petersen and Hubbart 2021 ; Xu et al 2020 ). Certainly, wastewater treatment plants (WWTPs) can remove more than 90% of MPs from wastewater, but this is insufficient, since millions of microplastics are still discharged into the environment every day by each WWTP (Ali et al 2021a , b ; Masiá et al 2020 ; Sol et al 2020 ; Menéndez-Manjón et al 2022 ). More specifically, it has been estimated that a WWTP releases between 0.01 and 2.97 × 10 2 particles per liter of effluent (Ali et al 2021a , b ; Liu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The article presents data on MP contents in municipal sewerage systems of a bigger European city. There are some data on different wastewater treatment plants (WWTP) available in the literature, [30][31][32], but a more comprehensive analysis of the entire municipal wastewater system often not exists. The entire wastewater system must be considered to track down undesirable entry paths into the environment.…”
Section: Introductionmentioning
confidence: 99%